PENGALAMAN BERSUA TUHAN: PERSPEKTIF WILLIAM JAMES DAN AL-GHAZALI - Komarudin, Komarudin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2012)
Experience of meeting God constitutes an interresting phenomenon and become the focus of interrest of many disciplines. Psychology and tasawuf are two disciplines which focusedly study this phenomenon applying different approaches. Ghazali is the representative of the dicsipline of tasawwuf and William James is the representative of the dicsipline of psychology. The both experts applied the different approaches in studying the religious experiences. Epistemological base on which William James used , has the scientific accountability but less accurate in the source of knowledge. In other side, Ghazali has a deep source of knowledge but less of rationality. An effort to compromise the both approach in order to study about the experience of meeting God will result in a comprehensive, deep, and objective depiction.***Pengalaman bersua Tuhan merupakan fenomena yang menarik dan menjadi titik perhatian banyak disiplin ilmu. Psikologi dan tasawuf merupakan dua disiplin ilmu yang memfokuskan kajiannya pada fenomena ini dengan menerapkan pendekatan yang berbeda. Ghazali adalah representasi dari disiplin ilmu tasawuf dan William James adalah representasi disiplin ilmu psikologi. Kedua ahli tersebut menggunakan pendekatan yang berbeda dalam mengkaji pengalaman keagamaan. Basis epistimologi yang digunakan oleh James memiliki akuntabilitas ilmiah namun kurang akurat dalam sumber pengetahuannya. Di sisi lain Ghazali memiliki sumber pengetahuan yang dalam namun kurang dari sisi rasionalitas. Upaya untuk mengkompromikan kedua pendekatan dalam rangka untuk mengkaji pengalaman bersua Tuhan akan menghasilkan penggambaran yang dalam dan obyektif.